Fabrication of soft, stimulus-responsive structures with sub-micron resolution via two-photon polymerization of poly(ionic liquid)s. Issue 8 (October 2018) - Tudor, Alexandru; Delaney, Colm; Zhang, Hongrui; Thompson, Alex J.; Curto, Vincenzo F.; Yang, Guang-Zhong; Higgins, Michael J.; Diamond, Dermot; Florea, Larisa
Graphical abstract: Abstract: Soft, stimulus-responsive 3D structures created from crosslinked poly(ionic liquid)s (PILs) have been fabricated at unprecedented sub-micron resolution by direct laser writing (DLW). These structures absorb considerable quantities of solvent ( e.g., water, alcohol, and acetone) to produce PIL hydrogels that exhibit stimulus-responsive behavior. Due to their flexibility and soft, responsive nature, these structures are much more akin to biological systems than the conventional, highly crosslinked, rigid structures typically produced using 2-photon polymerization (2-PP). These PIL gels expand/contract due to solvent uptake/release, and, by exploiting inherited properties of the ionic liquid monomer (ILM), thermo-responsive gels that exhibit reversible area change (30 ± 3%, n  = 40) when the temperature is raised from 20 °C to 70 °C can be created. The effect is very rapid, with the response indistinguishable from the microcontroller heating rate of 7.4 °C s −1 . The presence of an endoskeleton-like framework within these structures influences movement arising from expansion/contraction and assists the retention of structural integrity during actuation cycling.